An evaluation on its fifth anniversary of the council of europe’s framework convention for the protection of national minorities - Relaño Pastor, Eugenia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The year 1998 marked the advent of the new Council of Europe’s Framework Convention for the Protection of National Minorities (FCNM). It is legally binding and has been ratified by almost all of the Council of Europe’s members. The FCNM offers an objective, apolitical way of responding to the needs of minorities by agreeing minimal norms that must be met. It is a unique, legally binding instrument, offering individual protection with a collective dimension.In most countries there is intolerance and prejudice towards immigrants, asylum-seekers, and towards certain ethnic minorities. In particular, discrimination against Roma has continued across Europe at government and community level. If the FCNM is properly applied, it will put an end to this and many other injustices. Five years after it entered into force, it is time to assess the effectiveness of the monitoring of FCNM which is crucial for measuring and managing the protection of national minorities and for the promotion of tolerance throughout society. I will focus on the most significant problems that the Advisory Committee —the key monitoring body— have faced in the last five years and I will analyse the most outstanding issues related to the FCNM that States have failed to accomplish.
Keywords: Council of Europe; Protection of National Minorities